2020
DOI: 10.3389/fneur.2020.00333
|View full text |Cite
|
Sign up to set email alerts
|

Deciding Thrombolysis in AIS Based on Automated versus on WhatsApp Interpreted ASPECTS, a Reliability and Cost-Effectiveness Analysis in Developing System of Care

Abstract: Background: Automated ASPECTS has the potential of reducing interobserver variability in the determination of early ischemic changes. We aimed to assess the performance of an automated ASPECTS vs. ASPECTS interpreted for sent CT images on WhatsApp and to correlate these results with the outcome.Materials and Methods: Patients with anterior circulation stroke who had baseline NCCT and underwent successful IV-thrombolysis were included. NCCT-ASPECTS was assessed by two neuroradiologists, and discrepancies were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The remaining 20 studies were read full text. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The relevant data were extracted and the 2 reviewers independently further assessed the quality of the articles per the CHEERS and Philips checklists.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 20 studies were read full text. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The relevant data were extracted and the 2 reviewers independently further assessed the quality of the articles per the CHEERS and Philips checklists.…”
Section: Search Resultsmentioning
confidence: 99%
“…A general overview of the included studies, including the details of the reported AI applications, is provided in Table 2. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The majority of studies was published in 2019 or later. The studies were conducted in a range of medical specialties, yet ophthalmology was evidently the dominant field.…”
Section: General Overview Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar study analyzing relative Hounsfield unit density per region found a sensitivity of 45% and a specificity of 93% for a HU ratio threshold of < 0.94 and an area under the curve of 0.780 [ 24 ]. A study assessing RAPID@IschemaView automated ASPECTS found a performance equal to the agreement read of expert neuroradiologists [ 25 ].…”
Section: Discussionmentioning
confidence: 99%